On the Solution of Some Difference Equations (European Journal of Pure and Applied Mathematics, 2011)
We  obtain in this paper the solutions of the following difference equations x_{n+1}=((x_{n-3})/(±1±x_{n-1}x_{n-3})),n=0,1,...,where the initial conditions are arbitrary nonzero real numbers.